The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1002/app.1990.070410534
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic copolyimide membranes for high temperature gas separations: H2/CH4, H2/N2, and O2/N2

Abstract: SynopsisA series of high-molecular weight condensation polyimides prepared from pyromellitic dianhydride ( PMDA) or 3,3,4,4'-benzophenone tetracarhoxylic dianhydride (BTDA) with 4,4'-oxydianiline (ODA) and/or 1,5-diaminonaphthalene (NA), and a series of high-molecular weight condensation poly (amide-imides) prepared from trimellitic anhydride acid chloride (TMAC ) with ODA and/or NA were evaluated to determine, in the temperature region 50-250°C, the effect of polymer molecular structure on the permeability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Effect of Chemical Structure of Polyimides on Gas Permeability and Selectivity. Organic glassy polymers like polyimides are very promising as materials for membranes as they have excellent permselectivity and stability (Chem et al, 1984;Sykes and Clair, 1986;O'Brien et al, 1987O'Brien et al, ,1988Kim et al, 1988;Stem et al, 1989; Okamoto et al, 1989;Tanaka et al, 1989aTanaka et al, ,b, 1992a,b; Coleman and Koros, 1990; Buys et al, 1990; Kneifel and Peinemann, 1992). In the last decade, many efforts have been made to understand the relationship between the chemical structure of polyimide and its gas permeation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of Chemical Structure of Polyimides on Gas Permeability and Selectivity. Organic glassy polymers like polyimides are very promising as materials for membranes as they have excellent permselectivity and stability (Chem et al, 1984;Sykes and Clair, 1986;O'Brien et al, 1987O'Brien et al, ,1988Kim et al, 1988;Stem et al, 1989; Okamoto et al, 1989;Tanaka et al, 1989aTanaka et al, ,b, 1992a,b; Coleman and Koros, 1990; Buys et al, 1990; Kneifel and Peinemann, 1992). In the last decade, many efforts have been made to understand the relationship between the chemical structure of polyimide and its gas permeation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…4,4’‐ oxydianiline commonly abbreviated as ODA has been efficaciously used since a long time in the field of material chemistry for development of promising materials for membranes owing to their properties of excellent permselectivity and stability in the form of organic glassy polymers like polyimides . The derivatives of ODA displayed excellent thermal stability and increased membrane permeability due to the introduction of a rigid and bulky dianiline structure with inhibited rotation around −O− linkages.…”
Section: Resultsmentioning
confidence: 99%
“…The study of rPAI materials requires a polymerization technique to achieve a soluble polymer without solid state ring closure of the amic acid bond. The work of Imai and coworkers8 and Buys and coworkers9 both indicated that the ring closure of amic acid to imide was done in the solid state at elevated temperatures. We have used their techniques to prepare dense films of rPAI materials and have found that the solid state thermal imidizations resulted in a high level of defective dense films.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the historical background of polyamide imides was presented in a recent doctoral thesis7 along with excellent synthetic details of model compound studies. The synthesis of rPAI materials have been reported in the literature 8, 9. In both of these literature citations the polymer was formed in solution by the reaction of trimellitic anhydride chloride (TMAc) with aromatic diamine(s) to form the amide amic acid.…”
Section: Introductionmentioning
confidence: 99%